STUDI EMPIRIK: PERKEMBANGAN INVESTASI REKSADANA SYARIAH DI INDONESIA - Sjafruddin Sjafruddin; Risna Dewi (Program Studi Administrasi Bisnis, 2021)
To invest in the stock market, people are often constrained in value of investments and high risk. The existence of mutual funds in the investment world is expected to provide an opportunity for investors who have the money and limited investment information in the financial markets. For investors who have a value judgment ethic, Islamic mutual funds can be an option while considering investment risk and return.Mutual fund industry in Indonesia has improved steadily increasing both in number of mutual funds, investment units, and net asset value. Islamic mutual funds also experienced an increase in the number of issued investment products based on Islamic values by investment manager. However, the total investment or contribution to economic activity is still lower investment in the mutual fund industry as a whole.